SYNTHESIS AND CHARACTERIZATION OF SILVER NANOPARTICLES CONTAIN CURCUMIN AS AN EARLY CANDIDATE FOR ANTICANCER DRUG - Ersalina Nidianti; Devyana Dyah Wulandari; Fadlilah Nur Aini; Herliani Rahmania Sari (Universitas Muhammadiyah Magelang, 2021)
Cancer treatment can be done with tumor surgery, radiotherapy, immunotherapy, and chemotherapy. These treatments effectively kill cancer cells but have side effects and are resistant to patients. Based on this, further research is needed related to cancer drugs based on herbal plants, one of which is by using curcumin from Curcuma longa or turmeric in the form of nanoparticles to increase bioavailability and solubility. Especially silver nanoparticles with a mixture of curcumin. The aim of this study was to determine the characterization and screening of candidate activities to be used as anticancer drugs from curcumin extract and silver nanoparticles (AgNO3) containing curcumin carried out solubility test, thin layer chromatography (TLC) analysis, UV-Vis spectrophotometer analysis, and morphological analysis with XRD. The results obtained in this study were curcumin extract insoluble in water while silver nanoparticles could dissolve in water. TLC analysis on chloroform mixture: ethanol Rf = 0,92 and Rf = 0,94; chloroform: hexane obtained Rf = 0,36; Rf = 0,36: Rf 0,38; Rf = 0,3. While chloroform: benzene: methanol eluent has no Rf value. UV-Vis spectra obtained a maximum absorbance of 4,267 at a wavelength of 290 nm. The morphological analysis of XRD silver nanoparticles containing curcumin was 17,45 nm. In conclusion, curcumin extract and silver curcumin nanoparticles have the potential as initial candidates for anticancer drugs.